Radio frequency ablation for the intrauterine treatment of giant placental chorioangioma associated with fetal compromise: A case report. Issue 2 (19th October 2022) - Zhao, Bingyi; Yin, Lu; Chu, Wei; Wang, Fangna; Huo, Ping; Gao, Jian
Abstract: Giant placental chorioangiomas associated with fetal hyperdynamic circulation complications are rare to see. Here, we summarized a case of giant placental chorioangioma associated with fetal anemia and heart failure treated by radiofrequency ablation (RFA) combined with cordocentesis and intrauterine transfusion. The sonographic appearance of the placental chorioangioma was atypical which was isoechoic with unclear boundary. RFA was performed successfully at 27 weeks of gestation, when the chorioangioma has increased to 17.0 × 10.6 × 12.3 cm 3 . Unfortunately, intrauterine fetal demise was found on the first day after operation. After induction of labor, it was pathologically confirmed as placental chorioangioma. Abstract : A giant placental chorioangioma increased to 17.0 × 10.6 × 12.3 cm 3 was found at 27 weeks of gestation. Radiofrequency ablation was performed successfully. Unfortunately, intrauterine fetal demise was found on the first day after operation.